World-systems analysis : an introduction - Wallerstein, Immanuel Maurice (Duke University Press, 2004)
In World-Systems Analysis, Immanuel Wallerstein provides a concise and accessible introduction to the comprehensive approach that he pioneered thirty years ago to understanding the history and development of the modern world. Since Wallerstein first developed world-systems analysis, it has become a widely utilized methodology within the historical social sciences and a common point of reference in discussions of globalization. Now, for the first time in one volume, Wallerstein offers a succinct summary of world-systems analysis and a clear outline of the modern world-system, describing the structures of knowledge upon which it is based, its mechanisms, and its future.